Performance and internal organs of Japanese quails given kandis (Garcinia xanthochymus) fruit extract with different degrees of acidity - Suci, Dwi Margi; Rachman, Aulia; Malinda, Ratriana T.; Hermana, Widya (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
This research evaluated the performance of quail given drinking kandis acid fruit extract during the laying period. Layer Quails used this research for 6 weeks. A completely randomized design (RAL) with four treatments and three replications for 132 quails was used in this research. The treatments were control (P0) and supplementation kandis acid fruit extract to reach pH 4 (P1), pH 3 (P2), and pH 2 (P3). Kandis acid fruit extract was given twice per week during research. The variables were feed consumption, egg weight, hen day production, feed conversion ratio percentage of internal organs, and percentage of digestive tract. The results showed that supplementation from kandis acid fruit extract did not affect feed consumption, egg weight, hen day production, and feed conversion ratio. It can be concluded that the supplementation from kandis acid fruit extract at pH 4 – pH two did not have a difference in quail performance.